2019
DOI: 10.1111/gcb.14702
|View full text |Cite
|
Sign up to set email alerts
|

CO2 emissions from an undrained tropical peatland: Interacting influences of temperature, shading and water table depth

Abstract: Emission of CO2 from tropical peatlands is an important component of the global carbon budget. Over days to months, these fluxes are largely controlled by water table depth. However, the diurnal cycle is less well understood, in part, because most measurements have been collected daily at midday. We used an automated chamber system to make hourly measurements of peat surface CO2 emissions from chambers root‐cut to 30 cm. We then used these data to disentangle the relationship between temperature, water table a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 45 publications
(137 reference statements)
5
22
1
Order By: Relevance
“…At both the intact and burnt PSF transects, the lowest R eco flux rates occurred in January and March, when soil temperatures were at a minimum and the WT was close to the peat surface (Figure 3). Other studies have shown similar trends (Hirano et al., 2009, 2014; Hoyt et al., 2019; Jauhiainen et al., 2012; Jauhiainen, Takahashi, Heikkinen, Martikainen, & Vasander, 2005; Sundari, Hirano, Yamada, Kusin, & Limin, 2012). This is likely due to a reduced oxic zone in the peat upper layer, which results in reduced aerobic decomposition, and hence R eco emissions.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…At both the intact and burnt PSF transects, the lowest R eco flux rates occurred in January and March, when soil temperatures were at a minimum and the WT was close to the peat surface (Figure 3). Other studies have shown similar trends (Hirano et al., 2009, 2014; Hoyt et al., 2019; Jauhiainen et al., 2012; Jauhiainen, Takahashi, Heikkinen, Martikainen, & Vasander, 2005; Sundari, Hirano, Yamada, Kusin, & Limin, 2012). This is likely due to a reduced oxic zone in the peat upper layer, which results in reduced aerobic decomposition, and hence R eco emissions.…”
Section: Discussionsupporting
confidence: 56%
“…Other studies have shown similar trends (Hirano et al, 2009(Hirano et al, , 2014Hoyt et al, 2019;Jauhiainen, Takahashi, Heikkinen, Martikainen, & Vasander, 2005;Sundari, Hirano, Yamada, Kusin, & Limin, 2012). This is likely due to a reduced oxic zone in the peat upper layer, which results in reduced aerobic decomposition, and hence R eco emissions.…”
Section: Effect Of Burning On R Eco Emission and C Sourcessupporting
confidence: 61%
See 1 more Smart Citation
“…Additionally, the results of our physical fractionation show that even close to the estuary, DOC remains in the dissolved and fine colloid form (< 0.22 µm) and that flocculation processes might be limited. The large areas of coastal peatlands in the region might explain the relatively high fluvial organic carbon export to the South China Sea (Huang et al, 2017). The decrease in trace metal concentrations after the confluence might be influenced by shifts in physical fractionation and an increased proportion of colloidal form.…”
Section: From Degraded Tropical Peatlands To the Oceanmentioning
confidence: 99%
“…And fourth, retardation is likely along banks at high flows, as peatland rivers tend to overflow their channels, leading to backwater effects (Åkesson et al, 2015). A scalar model for runoff generation from peatland subcatchments nonetheless provides a simple building block for inclusion in discharge modeling in tropical catchments, or for estimation of DOC export (Hoyt et al, 2019).…”
Section: 1029/2019wr025411mentioning
confidence: 99%